Border, identity, everyday life: The South Slavs of Gara in state security documents (1945–1956) - Vukman, Péter (Études sur la Région Méditerranéenne, 2023)
The Baja Triangle, also known as Northern Bácska, geographically roughly included the area between Baja (in Hungary), Subotica and Sombor (in Serbia). It has been a multiethnic region for centuries, inhabited by Hungarians, Germans, and South Slavs. The physical proximity of the border and its separating function had a fundamental impact on the daily lives of the Hungarians and South Slavs living here, especially after 1948, when, because of the escalation of the Soviet-Yugoslav conflict, Hungarian-Yugoslav relations also became frosty. In my paper, I will examine how the fluctuating Hungarian–Yugoslav relations following World War Two affected the South Slavs living there in connection with Gara, a multiethnic village close to the Hungarian–Yugoslav border, how it affected their everyday life, their ideas about the border, their identity and their relationship with other nationalities.